Results of resection of forearm soft tissue sarcoma - Eiji Nakata; Tomohiro Fujiwara; Toshiyuki Kunisada; Ryuichi Nakahara; Haruyoshi Katayama; Takuto Itano; Toshifumi Ozaki (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Purpose Soft tissue sarcomas (STS) of the forearm are rare. We aim to assess their oncological and functional outcomes. Methods We retrospectively evaluated 34 patients who underwent surgical excision for forearm STS at our institution between 1993 and 2020. We analyzed postoperative Musculoskeletal Tumor Society rating scale (MSTS) and local recurrence-free survival (LRFS), metastasis-free survival, and overall survival (OS) rates. The significance of the following variables was determined: age, sex, histology, tumor size, Fédération Nationale des Centres de Lutte contre le Cancer grade, American Joint Committee on Cancer stage, surgical margin, unplanned excision, metastases upon initial presentation, receipt of chemotherapy, and radiotherapy (RT). Results The postoperative median MSTS score was 28. Bone resection or major nerve palsy was the only factor that influenced MSTS scores. The median MSTS scores in patients with or without bone resection or major nerve palsy were 24 and 29, respectively (P < 0.001). The 5-year LRFS rates was 87%. Univariate analysis revealed that the histological diagnosis of myxofibrosarcoma was the only factor that influenced LRFS (P = 0.047). The 5-year MFS rates was 71%. In univariate analysis, no factors were associated with MFS. The 5-year OS rates was 79%. Age was the only factor that influenced OS (P = 0.01). Conclusion In the treatment of forearm STS, reconstruction of the skin and tendon can compensate for function, while bone resection and major nerve disturbance cannot. Careful follow-up is important, especially in patients with myxofibrosarcoma, due to its likelihood of local recurrence.